PEMILIHAN MEDIA PROMOSI DENGAN METODE ANALYTIC HIERARCHY PROCESS (AHP) Studi Kasus: BSI Magelang - Candra Agustina (LPPM Universitas Bina Sarana Informatika, 2012)
Media promotion of an important part of a company, not least a college. Promotions conducted to get students according to the target set. BSI Magelang in promotion using the Brochures, Banners, Posters, Radio Advertising, Television Advertising, Newspaper Advertising, Internet. So that is more efficient promotion, must be known that the most effective media campaign. The results of this study will show the media promotion of consumer choice views of the various criteria. One method of decision support that can be used to solve such problems is Analityc Hierarchy Process. Data obtained from the questionnaires to the students spread BSI Magelang. The data were successfully acquired and processed using the software Super Decision 1.6.0. results obtained from the processing of these data shows that Palin ad is effective, according to respondents of TV commercials.Keyword: Analityc Hierarchy Proccess, Promotion, DSS.